A Fluorinated Bola‐Amphiphilic Dendrimer for On‐Demand Delivery of siRNA, via Specific Response to Reactive Oxygen Species. (26th October 2016) - Liu, Xiaoxuan; Wang, Yang; Chen, Chao; Tintaru, Aura; Cao, Yu; Liu, Juan; Ziarelli, Fabio; Tang, Jingjie; Guo, Hongbo; Rosas, Roseline; Giorgio, Suzanne; Charles, Laurence; et al.
Abstract : Functional materials capable of responding to stimuli intrinsic to diseases are extremely important for specific drug delivery at the disease site. However, developing on‐demand stimulus‐responsive vectors for targeted delivery is highly challenging. Here, a stimulus‐responsive fluorinated bola‐amphiphilic dendrimer is reported for on‐demand delivery of small interfering RNA (siRNA) in response to the characteristic high level of reactive oxygen species (ROS) in cancer cells. This dendrimer bears a ROS‐sensitive thioacetal in the hydrophobic core and positively charged poly(amidoamine) dendrons at the terminals, capable of interacting and compacting the negatively charged siRNA into nanoparticles to protect the siRNA and promote cellular uptake. The ROS‐sensitive feature of this dendrimer boosts specific and efficient disassembly of the siRNA/vector complexes in ROS‐rich cancer cells for effective siRNA delivery and gene silencing. Moreover, the fluorine tags in the vector enable 19 F‐NMR analysis of the ROS‐responsive delivery process. In addition, this ingenious and distinct bola‐amphiphilic dendrimer is also able to combine the advantageous delivery features of both lipid and dendrimer vectors. Therefore, it represents an innovative on‐demand stimulus‐responsive delivery platform. Abstract : A fluorinated bola‐amphiphilic dendrimer, sensitive to reactive oxygen species (ROS), is capable of on‐demand delivery of siRNA in ROS‐rich cancer cells. The unique bola amphiphilic feature endows this vector with the combined advantages of lipid and dendrimer vectors, while the fluorine tags enable the delivery process to be studied using 19 F‐NMR, opening up a new perspective on on‐demand stimulus‐responsive delivery.